Clonal monosomy of chromosome 21 in a case of myelodysplastic syndrome - Freitas, P. C. [UNESP]; Carvalho-Salles, A. B.; Mendiburu, C. F. [UNESP]; Ricci, O.; Fett-Conte, A. C. (Funpec-editora, 2011)
This study reports on a cytogenetic finding in a bone marrow examination of a 47-year-old male patient treated in the Hematology and Blood Transfusion Service of the Hospital de Base in Sao Jose do Rio Preto, Sao Paulo State, Brazil. The only alteration found at diagnosis of myelodysplastic syndrome (MDS) subtype refractory anemia with excess blasts (RAEB-2) was clonal monosomy of chromosome 21. The patient evolved to acute myeloid leukemia type M2 and died nine months after diagnosis. Clonal monosomy of chromosome 21, as the only cytogenetic abnormality in MDS, has only been reported three times previously. This uncommon cytogenetic abnormality in MDS has been associated with a poor clinical course, although more data will be needed to determine if this prognosis is invariable.
Keywords: Myelodysplastic syndrome; Monosomy 21; Clonal chromosomal abnormalities